Představy o mužském/chlapeckém vzhledu ve školních třídách - Irena Smetáčková; Helena Čechová; Karolína Klasová; Barbora Slavíčkvoá (Gender a Výzkum, 2013)
The article is focuses on the adolescent concept of male/boy appearance and its impact on the social position of boys in a classroom structure. Boys can reach a better social position if their appearance corresponds to group norms. Based on three qualitative studies it is proven that group norms consist of a set of requirements toward male appearance which differ from requirements toward female appearance both in content and strength. The results of partial surveys are discussed in the context of present international theoretical approaches and empirical evidences about the ideal of beauty in a gender perspective.